POJĘCIE „OSÓB BĘDĄCYCH W SZCZEGÓLNEJ SYTUACJI NA RYNKU PRACY” W ŚWIETLE USTAWY O PROMOCJI ZATRUDNIENIA I INSTYTUCJACH RYNKU PRACY - Staszewska, Ewa (Zeszyty Prawnicze, 2016)
Legal Notion „of Employees in a Particular Situation on the Labour Market”; in the Light of the Act of 2004 on Employment Promotion and Labour Market Institutions Summary The article refers to “employees in a particular situation on the labour market” in the light of the Act of 2004 on employment promotion and labour market institutions .The author points out that the risk of losing jobs varies. Certain categories of employees are more at risk than the others. From the social and economic point of view people are not equal when unemployment comes to the scene. Chances to find jobs are correlated not only with good economic condition but also with socio-demographic features of the jobless. The fact that some social groups are at higher risk of losing jobs creates the need to provide them with more specialized assistance from the State. It should be made possible for them to find steady jobs so that they do not get excluded from the labour market. That is why legislator has developed a catalogue of emploees particularly at risk who should be given priority when applying for a job. The unemployed listed in the catalogue can expect a number of legal instruments to prevent unemployment addressed to them.